Memories of paraguayan territoriality, achievements and cultural identity - Santos, Jose Carlos dos; Legal, Mirtha Lucia; Pereira, Luana Wiederkehr (Seven Editora, 2023)
This essay brings reflections on the production of written narratives about Paraguayan territoriality and cultural identity. It focuses on the use of a single data location: the Harvard Library and the Latin American Pamphlet Digital Collection. From the search for 8 bibliometric descriptors - nation, territory, physical aspects, border, security, people, migration and national identity - 5 works and an official document were listed to interpret the meanings and connections that these descriptors made it possible to make, from the authorship of the works, in the twentieth century. DOI:https://doi.org/10.56238/alookdevelopv1-186